Endomorphin-1 induced desensitization and down-regulation of the recombinant μ-opioid receptor - Harrison, C (2000)
1. Endomorphin-1 (E1) is a peptide with high affinity and selectivity for the μ-opioid receptor. The aim of this study was to determine if endomorphin-1 caused desensitization and down-regulation of the μ-opioid receptor expressed in Chinese hamster ovary cells. 2. Following 10 μM E1 pre-treatment, desensitization was assessed by measuring cyclic AMP inhibition, down-regulation was assessed by [(3)H]-diprenorphine ([(3)H]-DPN) binding and immunoblotting. 3. Pre-treatment of CHOμ cells with 10 μM E1 for 11 and 18 h caused significant reduction in cyclic AMP inhibition. (11 h=39.0±16.7%, 18 h 47.0±11.1% reduction). 4. At 18 h E1 pre-treatment there was an enhancement (4.5 fold) of cyclic AMP production under forskolin stimulated conditions accompanied by a small rightward shift in the concentration-response curve (pEC(50) control=7.8±0.3, pEC(50) E1=7.3±0.2) when cells were re-challenged with E1. 5. In membranes prepared from untreated and 0.5 h E1 pre-treated cells, addition of GTPγS produced a significant rightward shift in the concentration response curves for E1 displacement of [(3)H]-DPN (0 h K(i) control=7.86±0.11, GTPγS=7.37±0.15; 0.5 h K(i) control=7.92±0.12, GTPγS=7.36±0.08) This was not observed in membranes prepared from cells that had been treated with E1 for 18 h (18 h K(i) control=7.69±0.11, GTPγS=7.75±0.08). 6. In whole cells E1 treatment caused a rapid loss of cell surface receptors such that at 0.5 h there was a 30.5±1.5 reduction (this was unchanged for 18 h). In crude membranes a loss of receptors was also observed using radioligand binding or immuno-blotting protocols. 7. These data show that E1 causes desensitization and down-regulation of the rat μ-opioid receptor expressed in CHO cells. However, these two responses appear temporally distinct.